Analysis of Factors That Influence Decision Making Invest in Capital Markets in Millennial Generations - Irawati Junaeni (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2020)
This study aims to analyze the factors that influence the decision making of investors investing in the capital market. The sampling method used in this study was purposive sampling method, the sample used in this study was the millennial generation in Jakarta who had invested in the capital market. Sample size determination based on Slovin formula. The data used in this study are primary data in the form of questionnaires and secondary data in the form of library studies. The analysis technique in this study is simple linear regression and multiple linear regression. The results of research that have been carried out both in partial and simultaneous testing show that all variables, namely knowledge, risk, income, capital market training, and motivation have a significant positive effect on investment decisions.